Drivers of customer satisfaction and loyalty in service industries - Erjavec, Hana Šuster; Dmitrović, Tanja; Povalej Bržan, Petra (Journal of Business Economics and Management, 2016)
The relationship between customer satisfaction, customer loyalty and their antecedents, service output quality, quality of staff, corporate image, and price perception, is examined in the context of three service industries: use of the highway infrastructure, mobile telephone services, and hairdressing services. The research model was empirically evaluated for a large sample of respondents from a Central European country, using structural equation modelling. The results indicate that the four antecedents affect customer loyalty, and customer satisfaction acts as a mediator in all three service industries. However, the strength of the relationship between the constructs varies markedly across the industries, implying that competitive environment importantly determines the elements of service offering that lead to satisfaction and loyalty in a particular industry. The research findings contribute to a better understanding of which behavioural mechanisms and factors are a viable basis for increasing customer retention in a specific market structure. Managerial implications are discussed, and policy recommendations are offered.